Liderazgo ético en el trabajo en equipo en los docentes del Instituto Tecnológico Pedro Antonio del Águila Hidalgo Iquitos 2023 - Ruiz Reátegui, Claudia Isabel (2024)
This study aimed to evaluate the influence of ethical leadership on the improvement of teamwork among the teachers of the Pedro Antonio del Águila Hidalgo Technological Institute in 2023. A quantitative approach with a quasi experimental and causal correlational design was employed. The sample consisted of 60 teachers, divided into two groups: one control group with 30 participants and one experimental group with 30 participants. Pre and post tests were administered, revealing differences in the distribution of categories between the groups. In the control group, 33.4% obtained the regular category in the pre-test, while in the experimental group it was 60%. In the post-test, 90% of the control group achieved the very good category, whereas in the experimental group, 83.3% obtained the excellent category. Statistical analyses did not show significant differences in variances between the control and experimental groups, with F values of 1.736 and a p-value of 0.193, respectively. The t-test indicated no significant differences in mean scores between both groups in the pre-test, with a t-value of -1.119 and a p-value of 0.268. However, significant differences were observed in means in the post test, with an F value of 0.032 and a p-value of 0.859 for both groups, suggesting insufficient evidence to reject the null hypothesis of equal variances between the study groups. Additionally, a t-value of -8.670 was recorded, with 58 degrees of freedom and a p-value of 0.000. Therefore, it is concluded that ethical leadership significantly influences the improvement of teamwork among the teachers of the Pedro Antonio del Águila Hidalgo Technological Institute in 2023.